A heat-treatable Mg–Al–Ca–Mn–Zn sheet alloy with good room temperature formability. (September 2017) - Bian, M.Z.; Sasaki, T.T.; Suh, B.C.; Nakata, T.; Kamado, S.; Hono, K.
Abstract: A newly developed magnesium sheet alloy, Mg–1.1Al–0.3Ca–0.2Mn–0.3Zn (at.%), shows a large Index Erichsen value of 7.7 mm in a solution treated (T4) condition due to a weak basal texture developed by the trace addition of Zn. Subsequent artificial aging at 200 °C for 1 h (T6) significantly increases the 0.2% proof strength from 144 MPa to 204 MPa. This improvement in strength by the T6 treatment is associated with a dense distribution of monoatomic layer Guinier–Preston zones on the basal planes of the Mg matrix. Graphical abstract: